Ultra-Widefield Fundus Autofluorescence in Cytomegalovirus Retinitis. (2nd April 2020) - Tadepalli, Sameeksha; Bajgai, Priya; Dogra, Mohit; Singh, Simar Rajan; Sharma, Aman; Gupta, Vishali; Dogra, Mangat R.; Singh, Ramandeep
ABSTRACT: Purpose : To study the role of ultra-wide field (UWF) fundus autofluorescence (FAF) in the management of CMV (cytomegalovirus) retinitis. Material and methods : In this prospective, observational, non-randomized study, we followed up patients with active CMV retinitis on UWF fundus photograph (FP) and UWF-FAF. Results : A total of 16 patients (24 eyes) were studied. There were 13 males and mean age of patients was 37 (range 9–56) years. On UWF FP, out of 24 eyes, 13 (54.2%) had granular lesions, 3 (12.5%) had necrotizing pattern, 1 (4.1%) had a frosted branch angiitis (FBA), and 7 (29.2%) had a mixed pattern. UWF-FAF showed better delineation of borders of lesions in 7 eyes (29.1%), larger area of involvement in 8 eyes (33.3%), picked up 7 of 9 (77.77%) eyes of recurrence and helped differentiate cotton wool spots from retinitis lesion in one eye. Conclusion : UWF-FAF is useful in the management of CMV retinitis.